PRE-DESIGN OF A MICROGREENS PRODUCTION SYSTEM IN AN AQUAPONIC INSTALLATION WITH AN AEROPONIC IRRIGATION SYSTEM - Nur Khasanah, Septi
The increase in Indonesia's population in the last 2 years is quite significant. The population of Indonesia in 2021 was 272.68 million people, increasing in 2022 to 275.77 million people (BPS, 2022). The increase in population will have an impact on efforts to fulfill housing needs such as housing, shops and other public buildings. Thus, the number of land conversions is also increasing and causing land use competition between the non-agricultural sector and the agricultural sector, so that the amount of agricultural land is decreasing. Apart from the need for shelter, the need for food is also increasing (Prabowo et al., 2020). So, efforts need to be made to increase the productivity of agricultural land in terms of quantity and quality. As time goes by, people's interest in agricultural products is increasingly changing. Nowadays, people pay more attention to the nutritional value of the products they consume. One food that is quite popular among people is fresh food that contains lots of nutrients in the form of microgreens (Rokhmah et al., 2020). Microgreens are small vegetables that come from the seeds of various types of vegetables and only have cotyledons or the first pair of young leaves (Xiao et al., 2014). The main advantage of microgreens as a cultivated plant is their high nutritional content. According to research conducted by Xiao et al. (2012), it is known that microgreens have high amounts of nutrients and vitamins, reaching 4 - 40 times higher than mature plants. However, in running a microgreens business there are challenges that require innovation to overcome. One of the challenges is the appearance of fungus on the surface of the planting medium which causes microgreens to fall easily and rot. This can happen because the humidity level in the planting medium is too high and there is little air circulation (Salim et al., 2021). One environmentally friendly cultivation system that can be applied to increase the productivity of microgreens is the aquaponic cultivation system. Aquaponics is the activity of cultivating plants hydroponically along with cultivating fish via aquaculture (Effendi et al., 2015). The working principle of aquaponics is to utilize fish waste and fish food waste as nutrients for cultivated plants (Rahmadhani et al., 2020). Apart from that, aquaponics also uses cultivated plants as fish pond water filters and reduces ammonia levels which can interfere with fish survival so that they can be reused for fish farming (Wijayanti et al., 2019). In general, an aquaponic irrigation system supplies water to plant roots continuously. However, when combined with aeroponics, the provision of water is not carried out continuously but is regulated according to need. Aeroponic watering is carried out twice (morning and evening), each time for one minute through a nozzle that sprays water in the form of mist. Land kale plants have great potential to be developed as microgreens because they are rich in nutrients. In 100 g of land kale there are 29 calories, 3 g protein, 5.4 g carbohydrates, 0.3 g fat, 73 mg calcium, 1 g fiber, 50 mg phosphorus, 2.5 mg iron, 6,300 IU vitamin A, 0, 07 mg vitamin B1, 32 mg vitamin C, and 89.7 g water (Ansyari et al., 2022). The type of fish that is often used in aquaponic systems is freshwater fish. One type of freshwater fish that is very popular with Indonesian people is tilapia. The advantages of tilapia fish are their attractive color and relatively faster growth compared to other types of fish. Within 5 months, tilapia can grow to weigh 120 grams (Andriany, 2018). Apart from that, tilapia is also a fish that can survive in brackish water and is more adaptive to disease attacks, and has a very high tolerance to various kinds of environmental stress, including salinity, temperature, pH and oxygen levels (Khairuman & Amri, 2013). Tilapia also has quite prospective business opportunities. According to the Indonesian Ministry of Maritime Affairs and Fisheries, in 2021 tilapia production will reach 1.35 million tons with a value of 33.62 trillion (KKP, 2022). Based on the results of Biomass Production Research (Final Project 1), information was obtained regarding the use of appropriate planting media in the process of producing kale microgreens in an aquaponic system with an aeroponic irrigation system. The research results showed that perlite planting media produced microgreens with better quantity and quality compared to cocopeat and cotton planting media. R/C ratio analysis also shows that the use of perlite planting media has the highest value compared to the use of cocopeat and cotton planting media. A schematic of the kale microgreens production system can be seen in Figure 1.